Thermoset and thermoplastic polymer composite with date palm fiber and its behavior: A review - Shahidul Islam; Fahmida‐E‐ Karim; Md. Redwanul Islam; Md. Abu Saeed; Kazi Ashraful Alam; Mst. Mohini Khatun (SPE Polymers)
Abstract Date palm fibers possess mechanical properties to synthetic fibers, making them a promising material for fabricating sustainable composites. Date palm fibers exhibit particular hydrophilicity and good mechanical characteristics, which require for particular considerations in composite compositions. Date palm fibers are an incredibly adaptable kind of vegetable fiber which is often used in structural composites. Date palm has also demonstrated promise in a number of other applications, including construction, lighter materials, and sports products. The goal of this study is to present an extensive summary of the current status of research date palm fiber reinforcement composites. This article gives a summary and analysis of the most significant studies on thermoset and thermoplastic composites reinforced with date palm fiber. This document also provides a summary of the primary attributes of date palm fibers, discusses how to improve their characteristics chemically, describes how to create and characterize date palm fiber composites, and highlights prospects for further study. This paper concludes with a few essential suggestions and future directions that highlight the problems that need to be solved in more in‐depth research and possible composites industrialization. Highlights Overviewing the composites made from date palm fiber Different properties of date palm fibers Mechanical behavior of date palm composites Applications of date palm composite Future prospects of the date palm composites.